Animals in religion : devotion, symbol and ritual - Allen, Barbara, Rev. (London, UK : Reaktion Books, 2016)
Explores the role of animals within a wide range of religious traditions. Sacred writings and oral traditions through the ages contain countless myths, legends and stories of animals, forming a fascinating record of the ways animals have figured in our spiritual lives. Delving deeper, the author highlights the ways that our religious practices have honored and relied upon our animal brethren, whether as gods, sacrificial beasts or companion creatures. She examines the principle of ahimsa, or non-violence, in Jainism, Buddhism and Hinduism, as well as tza'ar ba'alei chayim in Judaism, the prohibition on inflicting suffering on living beings, revealing the importance of respect for life in faiths of all times and places. From ancient Egypt and East Asia to the druids, Celts and Vikings, to the indigenous cultures of Central America, this book reveals a unifying message: the interdependence and spiritual connection of all species.
"Animals in Religion explores the role and presence of animals within a wide range of religious traditions, from ensouled narratives within oral tradition to religious texts, myths and accompanying legends. Some of the material may have a familiar ring, such as the stories of St Francis of Assisi and Ganesha, but other, unusual facts also make an appearance. This book proposes a deeper respect for our four-legged, finned and feathered brethren. From the principle of ahimsa (non-violence) in Jainism, Buddhism and Hinduism, to the laws which relate to tza'ar ba'alei chayim (avoiding the suffering/pain of living creatures) in Judaism, we encounter the interdependence of life. The Jainist notion of 'reverence for life', the pronouncement in Genesis that 'it was good' and the Islamic belief that all species are Muslim allow us to come to a realization, or a deeper appreciation, that non-human animals have value in our religious traditions, as well as in our hearts and homes. The book examines animals not only in all the major monotheistic religions but in the beliefs of the Egyptian, Mesoamerican and Indigenous peoples of North America and Australasia as well as of the Vikings and Druids." -- Publisher's description
Animals in tribal and First Peoples' religions -- Animals in ancient Egyptian religion and mythology -- Animals in Celtic and Viking myth and ritual -- Animals in Judaism -- Animals in Christianity -- Animals in Islam -- Animals in Hinduism -- Animals in Jainism -- Animals in Buddhism -- Animals in religion in China and Japan.
Includes bibliographical references (pages 463-536) and index.
Keywords: Animals -- Religious aspects; Human-animal relationships -- Religious aspects; Scapegoat